A completely unique account of enumeration - van der Rest, Cas; Swierstra, Wouter (Proceedings of ACM on programming languages, 2022)
How can we enumerate the inhabitants of an algebraic datatype? This paper explores a datatype generic solution that works for all regular types and indexed families . The enumerators presented here are provably both complete and unique —they will eventually produce every value exactly once—and fair —they avoid bias when composing enumerators. Finally, these enumerators memoise previously enumerated values whenever possible, thereby avoiding repeatedly recomputing recursive results.